Effect of addition of some organic acids and creatine to the rations of fattening Awassi lambs in some cellular and biochemical blood parameters - Lazim, Jamil Sarhan; Al-Muhana, Hummam Hussein (Journal of Kerbala for Agricultural Sciences, 2018)
The high demand for red meat in the market should be accompanied by production to cover the current shortages in local and international markets (Badri 2010). Researches have focused on cheap and easy additions to achieve this goal. Antonio (2013) used creatine in order to provide lamb and obtaining increases in weight and muscle being the beginning of the composition of many amino acids. organic acids were added as feed additives but it did not lead to further improvement, the addition of creatine or organic acids or their mixture in the relations of Awassi sheeps. Twenty eight Awassi lambs were used into four treatments randomly with 7 lambs in each. The first treatment (T1) as a control group, and the second treatment (T2) the lambs were fed with 3 kg of organic acids/ton, the third treatment (T3) the lambs were fed with 1.2 kg of creatine/ ton and the fourth treatment (T4) with (1.5 kg of organic acids with 0.6 kg creatine / ton of feed). The experiment was designed according to the CRD design to demonstrate the impact of these additions on some cellular and biochemical blood parameters for fattening Awassi lambs, blood samples were drawn from the jugular vein in three periods (when the experiment started, 45 days and 90 days). Results showed the following: The statistical analysis of Table 2 showed no significant differences in the means of red blood cells (RBC), hemoglobin (Hb) and Hematocrit (PCV) for the three periods of blood parameters from Awassi lambs, while significant differences (P <0.05) in white blood cell (WBC) count were observed for the similar effect of blood drawn on day 45 and day 90 of the experiment, and it was significantly increased in all lambs that were fed on a mixture of organic acids and creatine (T4) as well as in lambs fed on creatine only (T3), while the lowest values ​​were observed in lambs with the second treatment (T2), which were fed on organic acids only. As for blood biochemistry criteria, Table 3 showed a significant effect (P <0.01) in the second drawn (45 days) in the concentration of triglycerides and urea and also the total protein in the third drawn, while no such differences were found in the concentrations of glucose and cholesterol for all the blood drawn.